Comparative Analysis of Impact of TENS and EMS on Treatment of Patients with Chronic Hemiplegia Caused by Stroke Using Fugl-Meyer Assessment Scale - Hardaha, Shilpa; Jain, Anu; Singh, Sumer; Tomar, Tapasya; Bakshi, Deepika (Asian Journal of Medical Research, 2022)
Background: The aim is to compare impact of TENS and EMS on treatment of patients with chronic hemiplegia caused by stroke using Fugl-Meyer assessment scale. Subjects and Methods: Subjects were divided into 2 groups of 20 each. Group A were hemiplegic subjects who were given TENS and group B were hemiplegic subjects who were given EMS. FMA, NDS and BI value were compared. Results: Left side was involved in 8 patients in group A and 11 in group B and right side in 12 in group A and 9 in group B. Type of stroke was ischemic in 5 in group A and 8 in group B and haemorrhagic in 15 patients in group A and 12 in group B. SBP was 120.4- and 68.4-mm Hg in group A and 124.6 and 70.2 mm Hg in group B. The mean pre- treatment FMA value in group A was 26.5 and post- treatment FMA was 41.7, in group B pre- treatment FMA value was 26.8 and post- treatment FMA value was 42.2. The mean pre- treatment NDS value in group A was 25.6 and post- treatment NDS was 18.4, in group B pre- treatment NDS value was 25.8 and post- treatment NDS value was 20.7. The mean pre- treatment BI value in group A was 32.5 and post- treatment BI was 50.2, in group B pre- treatment BI value was 33.2 and post- treatment BI value was 54.7. Conclusion: Physiotherapy is one of effective management in retaining strength and spasticity in stroke patients. Both TENS and EMS can help them improve their ability to move their hemiplegic lower extremity.